Window of hope / Nur Hazelen Mat Rusok and Junaidi Awang - Mat Rusok, Nur Hazelen; Awang, Junaidi (Faculty of Art and Design, 2021)
The window of hope interprets a feeling of an old mother waiting for the return of his estranged children, a window on which reflects the joy of being with grandchildren, keep asking of when they will return?... the same situation is felt by others who are separated from loved ones during the pandemic.. there are no words and no feelings that can describe the hopes of a mother awaiting the moment of their return.. a window full of loneliness and hope, .. how the long-awaited times will come or just hope.. Whether we think about it or not, hope is a part of everyone’s life. Everyone hopes for something. It’s an inherent part of being a human being. Hope helps us define what we want in our futures and is part of the self-narrative about our lives we all have running inside our minds.